Organization of gangliosides into membrane nanodomains - Sarmento, Maria J; Ricardo, Joana C; Amaro, Mariana; Šachl, Radek (FEBS letters, 2020)
Gangliosides are glycosphingolipids consisting of a ceramide base and a bulky sugar chain that contains one or more sialic acids. This unique structure endows gangliosides with a strong tendency to self-aggregate in solution, as well as in cellular membranes, where they can form nanoscopic assemblies called ganglioside nanodomains. As gangliosides are important biological molecules involved in a number of physiological processes, characterization of their lateral organization in membranes is essential. This review aims at providing comprehensive information about the nanoscale organization of gangliosides in various synthetic models. To this end, the impact of the hydrophobic backbone and the headgroup on the segregation of gangliosides into nanodomains are discussed in detail, as well as the way in which the properties of nanodomains are affected by ligand binding. Small size makes the characterization of ganglioside nanodomains challenging, and we thus highlight the biophysical methods that have advanced this research, such as Monte Carlo Förster resonance energy transfer, atomic force microscopy and approaches based on molecular diffusion.
Keywords: hydrofobní a hydrofilní interakce; diffusion laws; lipidové dvojvrstvy; GM1; ligandy; lipid bilayers; Cell Membrane; sacharidové sekvence; mikroskopie atomárních sil; nanodomains; Gangliosides; Lipid Bilayers; Hydrophobic and Hydrophilic Interactions; Ligands; rezonanční přenos fluorescenční energie; Humans; Microscopy, Atomic Force; diffusion; buněčná membrána; gangliosides; Fluorescence Resonance Energy Transfer; phase separation; MC-FRET; Carbohydrate Sequence; gangliosidy; AFM; lidé; membrane model systems